Analisis Pengaruh Generative AI Terhadap Personalisasi Iklan Real-Time Dan Dampaknya Pada Loyalitas Konsumen - Yoga Prasetya, Adhitya; Andanarini Minar Savitri , Dhian; Sumiyanti, Tri; Hermalia Putri , Anastasya Dina (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2025)
The rapid advancement of artificial intelligence, particularly Generative AI, has transformed the landscape of digital marketing by enabling firms to produce promotional content that is adaptive and personalized in real time. This study aims to examine the influence of Generative AI on real-time ad personalization and its subsequent impact on consumer loyalty. In addition, the study investigates the mediating role of real-time ad personalization in the relationship between Generative AI and consumer loyalty. A quantitative research approach with an explanatory research design was employed. Data were collected through questionnaires distributed to users of digital platforms who had previously received personalized advertisements. The data were then analyzed using Structural Equation Modeling (SEM). The findings are expected to demonstrate that Generative AI has a positive effect on both real-time ad personalization and consumer loyalty, and that real-time ad personalization functions as a mediating variable that strengthens this relationship. The results of the study are anticipated to contribute theoretically to the growing body of literature on AI-driven digital marketing. Moreover, the findings may serve as practical guidance for companies in designing more relevant, adaptive, and sustainable marketing communication strategies.